MÍDIAS DINÂMICAS EM BOOK APPs INFANTIS: a experiência do usuário infantil durante a prática de leitura - SANTOS, Daniella Carvalho Pereira dos (2017)
Research on the dynamic media of book apps and their effects on the children's user experience. The aim of this study was to analyze how the effects of the dynamic media of book apps affect the user experience during reading practice, based on the narrative immersion. The research was predominantly qualitative, characterizing itself as an exploratory, descriptive and explanatory research; to that end, rescued the state of the art in the subject in question in order to employ scientific support on the results obtained. Children of the 3rd year of elementary school in a public school in São Luís (MA) composed the universe of this research, which presents a non-probabilistic sampling, categorized as intentional or sampled by judgment, defined by saturation of information. They were used as instruments of data collection: interview, direct observation, video recording to record the information collected during the interaction test and the use of the loudspeaker technique, as well as application of the Likert scale satisfaction questionnaire. The research presents the results based on an interpretative analysis of the data, supported by the theoretical contribution referring to the aspects coming from the field of Design, especially the Design of Interaction. The analysis allowed us to infer that dynamic media affect the user experience during reading in a positive way, without harming the occurrence of narrative and playful immersion, complementing the sense of the narrative text in a digital environment.